High-Capacity Near-Infrared Optical Vortex Sorting and Detection by Nonlinear Dammann Vortex Grating - Hui Zhao; Ruwei Zhao; Qilu Liu; Yan Sheng; Tianxiang Xu (Photonics)
This paper demonstrates the sorting and detection of near-infrared vortex light using a nonlinear Dammann vortex grating. By incorporating a forked structure into the nonlinear Dammann grating, the resulting nonlinear Dammann vortex grating is capable of converting near-infrared Gaussian light into a visible vortex array. The array comprises 49 independent detection channels, each of which can precisely control the inherent topological charge values. When the topological charge value of a detection channel’s vortex light matches that of the incident vortex, the vortex degenerates into a Gaussian spot, thereby enabling the detection of the incident vortex’s topological charge. Our experimental results show that this grating, with its 49 independent detection channels, can detect the topological charge values of vortex light in the near-infrared range from l = −12 to +12 in real-time. Compared to existing solutions, this grating offers enhanced versatility and has potential applications in optical communication systems for the transmission, reception, and multiplexing of OV beams.